Building a School Quality Culture Through the Implementation of TQM (Total Quality Management) - Gilang Dwi Kurniawan; Marini Marini; Edi Fakhrin; Maulana Akbari; Aslamiah Aslamiah; Celia Cinantya (Journal of Educational Sciences, 2026)
The advancement of technology and the dynamics of the digital era have brought significant changes to all aspects of life, including education. Schools, as educational organizations, are required to adapt and improve the quality of their services in order to remain competitive in an increasingly demanding environment. One strategic approach widely implemented to ensure educational quality is Total Quality Management (TQM), which focuses on customer satisfaction, continuous improvement, and the involvement of all organizational elements. The implementation of TQM in the educational context is considered capable of bridging the gap between graduates’ competencies and the 21st-century skills demand, while also strengthening the school’s quality culture. Through a literature review of various journals, books, and research findings, this article analyzes the fundamental principles of TQM, the supporting factors for its success, and its contribution to building a quality culture in schools in the digital era. The findings indicate that TQM not only enhances school management effectiveness but also establishes a foundation for a proactive, collaborative, data-driven, and customer-focused organizational culture. Therefore, TQM serves as a relevant strategic approach to strengthen competitive advantage and foster a quality culture in schools amid the increasingly complex digital transformation.